Haematological and iron-related parameters in male and female athletes according to different metabolic energy demands - Milic, R.; Martinovic, J.; Dopsaj, M.; Dopsaj, V. (European Journal of Applied Physiology, 2011)
We investigated the iron-related haematological parameters in both male and female athletes participating in different sporting disciplines necessitating different metabolic energy demands. A total of 873 athletes (514 males, mean age: 22.08 ± 4.95 years and 359 females, mean age: 21.38 ± 3.88 years) were divided according to gender and to the predominant energy system required for participation in sport (aerobic, anaerobic or mixed) and haematological and iron-related parameters were measured. For both male and female athletes, significant differences related to the predominant energy system were found at a general level: male (Wilks` ? = 0.798, F = 3.047, p < 0.001) and female (Wilks` ? = 0.762, F = 2.591, p < 0.001). According to the ferritin cutoff value of 35 µg/L, whole body iron and sTfR significantly differed in all three groups of male and female athletes (p < 0.001). The percentage of hypochromic erythrocytes in male athletes was significantly higher only in those who required an anaerobic energy source (p < 0.001), whilst in the females hypochromic erythrocytes (p < 0.001) and haemoglobin (anaerobic, p = 0.042; mixed, p = 0.006) were significantly different only in anaerobic and mixed energy source athletes. According to the ferritin cutoff value of 22 µg/L, in females, whole body iron, sTfR and hypochromic erythrocytes were significantly higher in all three groups of athletes than those below the aforementioned cutoff value (p < 0.001). We conclude that the predominant energy system required for participation in sport affects haematological parameters. sTfR and body iron proved to be reliable parameters for monitoring the dynamics of iron metabolism and could contribute to successful iron-deficiency prevention.